1996
DOI: 10.1007/bf02172349
|View full text |Cite
|
Sign up to set email alerts
|

Hand preference and hand skill in children with autism

Abstract: Hand preference and hand skill was assessed in two broad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 15 publications
9
58
0
2
Order By: Relevance
“…These factors limit the generalizability of the results (e.g. to females and individuals who are left handed or lack handedness, which may be more common in autism (Cornish & McManus, 1996)) and suggest that replication with a more diverse sample is required. Finally, given recent work demonstrating that neural activation is related to how individuals visually scan face stimuli (Dalton et al, 2005), it is possible that our results may in part reflect abnormal visual face scanning in the clinical groups.…”
Section: Discussionmentioning
confidence: 99%
“…These factors limit the generalizability of the results (e.g. to females and individuals who are left handed or lack handedness, which may be more common in autism (Cornish & McManus, 1996)) and suggest that replication with a more diverse sample is required. Finally, given recent work demonstrating that neural activation is related to how individuals visually scan face stimuli (Dalton et al, 2005), it is possible that our results may in part reflect abnormal visual face scanning in the clinical groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies which have used laterality judgements in autism have not necessarily found group differences (David et al, 2010). Previous studies into handedness in ASD have shown that many people with ASD are ambidextrous and may show an ambiguous handedness profile switching arbitrarily between left and right (Cornish and McManus 1996;Soper et al 1986). This could make it more difficult for them to make judgements about laterality due to confusion between left and right.…”
Section: Egocentric Transformations Taskmentioning
confidence: 99%
“…Umansky et al (2003) found a left-hand preference of 33% in a group of 145 patients with Rett syndrome. Cornish and McManus (1996) assessed young (3-5 years) and older (11-13 years) children with autism (N=35), 26 children with learning disabilities, and 89 typically developing (TD) children. Hand preference was measured three times using a set of 10 symmetrically presented unimanual preference tasks (e.g.…”
Section: Introductionmentioning
confidence: 99%